The charm: a contribution to modern and mediaeval anthropology - Gifford, Douglas J. (1973)
One of the most serious difficulties in the historical study of folklore lies in the paucity of primary evidence. What we know of to-day as folk-tradition is rarely written about or commented on in the documents of the Middle Ages. Books of penance deal with superstitiones and other beliefs, but only in passing and without going into reliable detail as to what they consisted of, and even Burchard of Worms’ prohibitions, inte- resting as they are, leave much unsaid. This paper attempts to bring into relief one single aspect of folk-belief which is well documented, and which merits more attention than it has hitherto received: the charm.